Irlanda na revista Nós. Apuntamentos para un estudo das relacións culturais (II) - Allegue Leira, Alberto (Madrygal. Revista de Estudios Gallegos, 2011)
The cultural journal Nós, during its publication years, regularly featured pieces about Ireland and its culture. The two main contributors to the topic were Otero Pedrayo and Vicente Risco and their interest arose, together with an effort to consolidate a identificatory discourse based on the Celtic strain, from the internal debates within the pre-war nationalist movement as well as the utilization by the two Ourensians of the Irish example as a strategic model for the Galicianism of the twenties. The vision of Ireland reflected in Nós had initially a political slant, but the interests of editors and readership alongside the surrounding political atmosphere led to an evolution towards more literary and historic aspects. Precisely the same interests, shared by Otero and Risco (to reassert their strategic nationalist proposal and consolidate their own position), guided the adaptation of the Irish reality of the twenties to the ‘fitting’ version that reached Nós readers.
Keywords: Galiza-Ireland; cultural relations; Nós; galician nationalism; irish literature.